Individual policy preferences for vocational versus academic education micro level evidence for the case of Switzerland - Marius R. Busemeyer; Maria Alejandra Cattaneo; Stefan C. Wolter (Max Planck Institute for the Study of Societies, 2010)
This paper uses an original dataset from a survey conducted in Switzerland in 2007 to explore the dynamics of education policy preferences. This issue has largely been neglected so far as most studies on welfare state attitudes do not look at preferences for education. We argue that education policy preferences vary along two dimensions: the distribution of resources across different sectors of the education system (i.e. vocational training vs. academic education) and the level of investment in education both from public and private sources. With regard to the former, the findings suggest that individual educational experience matters most, i.e., individuals prefer to concentrate resources on those educational sectors that are closest to their own educational background. With regard to the second dimension, we find that affiliation to partisan ideologies matters much more than other variables. Proponents of the left demand more investment both from the state as well as from the private sector and oppose individual tuition fees. – – Dieses Papier untersucht die Dynamik bildungspolitischer Präferenzen auf der Mikroebene. Dabei werden Daten aus einer eigenen Erhebung verwendet, die im Jahr 2007 in der Schweiz durchgeführt wurde. Die Untersuchung bildungspolitischer Präferenzen wurde in der einschlägigen Literatur zur Untersuchung von wohlfahrtsstaatlichen Einstellungen bisher vernachlässigt. Wir zeigen, dass bildungspolitische Präferenzen auf zwei Dimensionen zu verorten sind: zum einen die Verteilung von öffentlichen Mitteln auf verschiedene Bildungssektoren (berufliche vs. hochschulische Bildung) und zum anderen das Gesamtniveau der Bildungsausgaben. In Bezug auf die erste Dimension stellen wir fest, dass der individuelle Bildungshintergrund sehr prägend ist. Die Befragten unterstützten die Konzentration von öffentlichen Mitteln in denjenigen Bildungsbereichen, die sie aus der eigenen Bildungskarriere kennen. In Bezug auf die zweite Dimension lassen sich hingegen starke ideologische Effekte feststellen. Individuen, die sich ideologisch im linken Spektrum verorten, fordern mehr Bildungsausgaben vonseiten des Staates und des Privatsektors und lehnen Studiengebühren eher ab.
Keywords: 300